Experimental study and numerical simulation of all‐steel buckling‐restrained brace with distributed inspection windows. (14th February 2022) - Wan, Chunfeng; Xie, Liyu; Li, Lin; Xue, Songtao; Tang, Hesheng; Zhang, Li
Summary: This paper presents a novel all‐steel seismic‐resistant, buckling‐restrained brace (BRB) which can be easily detached from its steel core for post‐seismic inspections. This allows inspectors to quickly determine if the BRB needs to be replaced to reduce the impact of seismic aftershocks. The weld toes of brace stiffeners were specially smoothed to reduce the residual stress and stress concentration, thereby improving the low‐cycle fatigue performance of the brace. Two identical restraining units were connected by high‐strength bolts. A small air gap was provided by annular gaskets between the core and the restraining system to allow for lateral expansion of the core plate under compression. Five specimens were tested under different cyclic loading protocols to investigate the performance. The hysteretic behavior, compression strength adjustment factor, equivalent viscous damping ratio, failure modes, and deformation of the restraining system were analyzed. The multi‐wave buckling deformation of the core was studied in detail to provide a basis for the accurate calculation of the number of contact points. Finite element analyses were performed to compare the response with test results, which proved the structure of the novel BRB to be reasonable except for the compression strength adjustment factor of some specimens, which was greater than 1.3. A damage assessment method was proposed to evaluate the working status of the newly designed BRB after an earthquake.